Net emission coefficient of complex thermal plasmas used in SWNT synthesis. (28th December 2018) - Hannachi, R; Nasr, S Ben; Cressault, Y; Teulet, Ph; Béji, L
Abstract: The calculation of net emission coefficient NEC is done for mixtures He–Ar/N2 –[C100− x − y − z, B z, Ni x /Co x, Y y ] used in the synthesis of single-wall carbon nanotubes SWNTs by arc discharge technique, at pressure of 60 kPa and at temperature interval going from 1 kK to 30 kK. These mixtures contain helium–argon as a gaseous atmosphere, nitrogen–boron as a doping atoms and a carbon anode filled with yttrium–nickel/cobalt as catalysis. Different proportions of metallic catalysts are considered going from 0.01 atomic% (at%) to 5 at%. Whereas for doping atoms the concentration amounts are much higher and do not exceed 8 at% for boron and 50% for nitrogen. The results of NECs are obtained by summing over all wavelengths, the contributions of atomic and molecular continuum, results of free–free and free–bound transitions, and line and molecular bands emissions corresponding to bound–bound transitions. Doppler broadening, resonance, van der Waals, electron and ion Stark broadening are taken into account for the calculation of the lines widths. As Stark broadening is the most important broadening mechanism at intermediate and high temperature, an empirical correction factors determined for some resonance lines, are added to the semi-empirical Stark formulas for a best reproducing of the experimental Stark widths. The comparisons of the NECs of the pure plasmas of argon, helium, nitrogen and carbon to those given in literature present an acceptable agreement. For the studied mixtures containing He–Ar/N2 –[C100− x − y − z, z B z, Ni x /Co x, Y y ], the obtained results show that the addition of boron or the nitrogen induces a few little changes in the NEC, in contrary to the metal catalysts where we noted a considerable increase in the plasma emission especially at low temperatures. The effect of the addition of yttrium in carbon anode even in a small amount (<0.1 at%) affects strongly the NEC compared to that of cobalt or nickel which have given similar results.